Physiological and Chemical Changes During Harvest Maturity in Peach Cultivars - Gercekcioglu, Resul; Filiz, Ali (Asian Journal of Chemistry, 2010)
Experiments were conducted in 2002 and 2003 with `J.H. Hale', `Loring' and `Dixigem' peaches. The optimum picking period for long-term shelf life corresponds to the period at which the respiratory activity of fruits is minimum or slightly late in climacteric fruits. However, slightly late period is the more reliable date for harvesting. Respiration rates were found 26.59 and 29.40 for J.H. Hale, 35.19 and 39.95 for Loring and 35.77 mL CO2 (kg h) for Dixigem (2002 year) in two years. On the other hand, at the maturing date, several chemical and physical changes were also observed which are suitable for optimum harvest criterion. The criteria like ground colour, flesh colour, flesh firmness, TSS, maturity ratio and sensory analyses score were observed for all cultivars.